Kontribusi Guru Pendidikan Agama Katolik Pegawai Negeri Sipil dalam Hidup Menggereja di Paroki Santo Yosep Delitua - Maduma Arihta Br Sinurat; Johannes Sohirimon Lumbanbatu (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2023)
The purpose of this research focuses on the contribution and driving factors of Catholic Religious Education Teachers who are Civil Servants (PNS) in the Parish of St. Joseph Delitua. This study employs a qualitative approach with data collection techniques including observation, interviews, and documentation. Catholic Religious Education Teachers have a special role in imparting the values of the Kingdom of God to students in schools and are considered as messengers of God and apostles of Christ who introduce God's love to the world. They also contribute to the mission and service of the Church. This research aims to delve deeper into the contribution and motivating factors for Catholic Religious Education Teachers who are PNS in the Parish of St. Joseph Delitua to participate in church life. The contributions of Catholic Religious Education Teachers include dual roles as preachers and teachers, pastoral workers, and religious community builders. This study is expected to provide a better understanding of the contribution and motivation of PNS Catholic Religious Education Teachers in their church involvement in the Parish of St. Joseph Delitua. Furthermore, this abstract also outlines the theoretical framework which includes the five pillars of church ministry: Liturgy, Kerygma, Diakonia, Koinonia, and Martyria, as well as the role of Catholic Religious Education Teachers in fulfilling their duties as educators and preachers. Catholic Religious Education Teachers have the responsibility to educate, guide, and proclaim the Word of God to students so that they can follow the teachings of Jesus. This research utilizes a qualitative method with snowball sampling technique for sample selection. The research data consists of primary and secondary data collected through observation, interviews, and documentation. The findings of this research will discuss the contribution of PNS Catholic Religious Education Teachers based on the five pillars of the church in the Parish of St. Joseph Delitua